(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the role of digital technologies in teaching pharmacology within modern medical education. The study examines the pedagogical significance of integrating digital tools such as multimedia resources, virtual laboratories, simulation-based learning, and online platforms into the educational process. It highlights how these technologies enhance students’ understanding of complex pharmacological concepts, improve knowledge retention, and promote independent learning. In addition, the impact of digital technologies on students’ motivation, engagement, and development of clinical reasoning skills is discussed. The findings suggest that the effective implementation of digital technologies significantly improves the quality of pharmacology education and prepares students for professional medical practice.